Assessing the Need for the Implementation of Specialized English Conversation Clubs for Ecotourism Students - Estefania Maldonado; Sulaya Bayancela; Edison Salas; Elsa Basantes (European Scientific Journal, ESJ, 2019)
This paper evaluates the need to implement specialized conversational clubs in English for ecotourism students to improve their communication skills. This study was conducted at the Escuela de Ecoturismo, Escuela Superior Politécnica de Chimborazo, Ecuador. Survey questionnaires were applied, to forty-one students from 4th to 8th level and eighteen lecturers, to collect their opinion regarding the implementation of specialized English conversation clubs. The results showed that both students and teachers agreed that there is a need for implementing English Conversation Clubs.